Acupuncture at Waiguan (SJ5) and sham points influences activation of functional brain areas of ischemic stroke patients: a functional magnetic resonance imaging study - Qi, Ji (Medknow Publications & Media Pvt Ltd, 2014)
Most studies addressing the specificity of meridians and acupuncture points have focused mainly on the different neural effects of acupuncture at different points in healthy individuals. This study examined the effects of acupuncture on brain function in a pathological context. Sixteen patients with ischemic stroke were randomly assigned to true point group (true acupuncture at right Waiguan (SJ5)) and sham point group (sham acupuncture). Results of functional magnetic resonance imaging revealed activation in right parietal lobe (Brodmann areas 7 and 19), the right temporal lobe (Brodmann area 39), the right limbic lobe (Brodmann area 23) and bilateral occipital lobes (Brodmann area 18). Furthermore, inhibition of bilateral frontal lobes (Brodmann area 4, 6, and 45), right parietal lobe (Brodmann areas 1 and 5) and left temporal lobe (Brodmann area 21) were observed in the true point group. Activation in the precuneus of right parietal lobe (Brodmann area 7) and inhibition of the left superior frontal gyrus (Brodmann area 10) was observed in the sham group. Compared with sham acupuncture, acupuncture at Waiguan in stroke patients inhibited Brodmann area 5 on the healthy side. Results indicated that the altered specificity of sensation-associated cortex (Brodmann area 5) is possibly associated with a central mechanism of acupuncture at Waiguan for stroke patients.